Sosialization of Chitosan as Natural Preservation for Palm Tree’s (Arenga pinnata Merr.) Sap in Akelamo, Central Oba - Albaar, Nurjana; Rasulu, Hamidin; Husen, Janiah; Wulansari, Angela (Altifani Journal: International Journal of Community Engagement, 2022)
Palm tree’s (Arenga pinnata Merr.) sap is the main ingredient for palm sugar. Palm tree’s sap is obtained by tapping the male flowers of palm tree. The sap is rich in sugar thus it is easy to be fermented. Palm farmers in Akelamo Village use soap as a preservation agent to prevent fermentation during the taping and loading period before the sap is cooked. Soap is a non-food product which is unsafe to be used in food product. Based on this fact, the community service program was designed to educate and share information about the danger of non-food preservation agent in food product, and also introduce chitosan as potential natural preservation to prevent fermentation process on palm tree’s sap among the palm farmers in Akelamo Village. There were four activities that had been done, such as discourse about food preservation and chitosan as natural preservation agent, workshop about how to apply chitosan to prevent fermentation during palm tree tapping, workshop about how to make palm sugar, and interactive dialogue with palm farmers. All the activities were done succesfully. The farmers were actively participated in every activity during the program.